Short selling restrictions in the EU and the US: a comparative analysis. Issue 2 (2nd July 2016) - Howell, Elizabeth
ABSTRACT: In the EU, short selling rules were introduced in 2012 (the 'Regulation'), largely as a consequence of the sovereign debt crisis. The influence of the crisis is evident in the Regulation, which restricts short selling in the sovereign debt markets, as well as the short selling of shares. In contrast, the US has had short selling rules in place since the 1930s. Following the financial crisis, although short selling regulation did not form a key priority on the international G20 reform agenda, the SEC subsequently implemented a number of new restrictions. This article analyses the choices made in both jurisdictions concerning short selling restrictions. Some similarities exist, but divergences are also evident, not least in the absence of constraints on sovereign debt in the US. Further, aside from the sovereign debt restrictions, the US rules are in fact more onerous than those in the EU. This article suggests that this outcome can, perhaps, be explained in part by political pressures brought to bear on the SEC following the financial crisis. Turning to the EU, although the Regulation's passage was also a highly politicised affair, some of the more interventionist proposals could be subsequently watered down during the lengthy negotiation process.